Amine Borane Based Hydrogen Carriers: An Evaluation - Müller, Karsten; Stark, Katharina; Müller, Benjamin; Arlt, Wolfgang (Energy & Fuels, 2012)
Liquid organic hydrogen carriers (LOHCs) represent a new concept for energy-storage. LOHCs are able to store a considerable amount of hydrogen and release it on demand without being consumed themselves. A variety of different substances has been proposed recently. One promising group of potential carriers is amine borane based compounds. This contribution introduces the LOHC concept and gives a review over the amine borane based hydrogen carriers. An energetical evaluation using Aspen Plus was performed, and overall efficiencies were calculated. An energy storage system based on azaborines reaches efficiencies of up to 30%. This study shows that still intensive research on synthesis, regeneration, long-term stability, liquefaction, and toxicity is needed before this technique is marketable.